Informal education for the technification of agricultural production in urban orchards - Murcia Rodríguez, Jennifer Catalina; Quimbayo Feria, Adriana (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Urban agriculture allows the production of food, especially fruits, vegetables and aromatic plants, contributing to the reduction of the ecological footprint and self-sufficiency. Urban agricultural production is a global trend, in Colombia it is a practice to help mitigate environmental pollution and reduce the purchase of basic foods, which for example today due to inflation issues, their costs have increased, reducing their number in the homes.